Introduction: Circumpolar Ecosystems in Winter II - Scott, Peter A. (ARCTIC, 1993)
The second meeting of winter researchers was hosted by the Churchill Northern Studies Centre at Churchill, Manitoba, 12-17 February 1992. The outdoor workshop-sessions began with the "Sundown Walkabout," which coincided with the onset of a traditional arctic blizzard. . There were some 35 poster and oral presentations at the symposium, including an invited global change session. The presentations included topics such as snowmelt processes, the strategies of terrestrial and marine plant and animal populations that endure winter, and northern presentations. It is hoped that such a collection will serve to broaden our perspectives by offering the position that winter is the ambient condition in northern systems and summer conditions develop each year within this context. The study of winter therefore is fundamental to understanding future global change. Winter phenomena and the adaptations of northern indigenous peoples to these conditions are important examples for consideration in future scenarios. A workshop introduced participants to local winter conditions and how different cultures have adapted to this environment, with examples including the modern community as well as 18th- and 19th-century European pioneers. Inuit lifestyles were discussed and there were opportunities to participate in igloo building, sleeping outside, and testing traditional clothing during severe conditions. In addition, participants were instructed in the preparation of typical winter clothing, including lessons in stitching techniques and the sizing of handwear and footwear patterns. Traditional skin clothing, tried and tested over the millennia, was the standard for comparison with samples of other types of outdoor apparel, including natural materials such as down, wool, and cotton as well as the latest synthetics. . An example of a more moderate winter environment was explored during the undersea ice dive conducted by a Fisheries and Oceans Canada dive team while workshop participants viewed the proceedings live on a video monitor ...